Medicosocial Rehabilitation of Children Using Social Services - Effectiveness of Ergotherapeutic Activities - Danelina Vacheva; Iskra Petkova (Research Highlights in Disease and Health Research Vol. 5, 2023)
Socio-pedagogical and medico-social work with disadvantaged children requires professional competences adequate to the dynamic social changes associated with preparing children for independent and independent living. This issue is particularly relevant for children with disabilities when they are raised outside the family environment and is subject to the measure of a Family-type accommodation center. This determines the need for the development of an appropriate occupational and ergotherapeutic program that is appropriate to the age and individual health characteristics of the children, raiseds in a Family-type accommodation center setting and assist in the process of forming independent living skills. The purpose of this Communication is to present an author’s program on occupational therapy and ergotherapy to be included in the medico-social rehabilitation of disadvantaged children. Materials and Methods: Were conducted clinical studies (systematization of the medical documentation of disabled children); functional tests: „Activities of daily living“ (ADL) test, „Leisure management“ test, „Independent Living Skills“ test; sociological methods and statistical methods (SPSS, Wilcoxon rank test, Student’s t-test). Results and Analysis: The data from the statistical processing of the results confirm the working hypothesis that the applied occupational therapy program has a positive effect on the development of skills for independent living in children raised and educated in social services. Conclusion: The study shows that there is a need for the implementation of occupational and ergotherapy programs that stimulate the development process of disadvantaged children to improve self-care and life skills, as well as the acquisition of professional habits. The various and meaningful activities provided in their individual programs support the process of acquiring a set of knowledge and skills that they will need in the future independent life.